Wasathiyyah Islam as the Road to Moderatism in Indonesia - Abdurrohman Kasdi (Al-Albab, 2019)
The article aims to explore the implementation of al-wasathiyyah concept as a way towards achieving moderatism, as well as to see the discourse of Islam and moderation in Indonesia. The method is qualitative with religious sociological approach. Religious sociological approach is used because the wasathiyyah concept is tightly tied to the religion and society. The results of the research show that wasathiyyah Islam has the correlation to ethics and moderate traditions which are considered as a form of virtue. Moderate tradition in Islam in Indonesia includes several aspects of life, including: first, moderate in its thought and movement, which is reflected by the belief that is in line with the nature and ibadah that promotes world prosperity. Second, moderate in aqidah that is in line with the fitrah or nature of mankind, including in tolerance, consistence, and balance. Third, moderate in practicing Islamic teachings that is in accordance with human ability and not burdensome. Fourth, moderate in its method (manhaj). Fifth, moderate in reform and ijtihad. Through wasathiyyah Islam, Indonesian muslims are accustomed to a set of thoughts, behaviors, and actions that promote the spirit of moderation. Moreover, Indonesian Muslims are willing to consciously let go of their primordial religious bonds in favor of moderation. Therefore, waasathiyyah Islam is a concrete realization of a socio-political structure that is deeply rooted since the beginning, not a new diction that is used to describe the mindset of a certain group